The Role of Fractal Micro-Pore to Absorption of Methane Gas, Case Study: Coal of Tanjung Formation, Arang Alus Area, Banjar District, South Kalimantan, Indonesia - Sugeng Raharjo; Basuki Rahmad; Ketut Gunawan; Budi Prayitno (UIR PRESS, 2022)
The Tanjung Formation is one of the coal bearing formations in the Barito Basin, South Kalimantan. The coal seams in the Tanjung Formation in the Arang Alus area have 4 (four) seams,there are seam A, B, C, and D. The age of these coal seams are Eocene - Oligocene with a thickness between 0.5 - 2 meters. This study aims to determine the characteristics of micropore fractal and methane gas absorption from coal samples taken by channel sampling on exposed coal in the open pit. The method used is SEM analysis, vitrinite reflectance (Ro,max), adsorption isotherm, and fractal calculation. The four coal seams based on vitrinite reflectance values (0.52 %- 0.62 belong to the sub-bituminous rank. Based on the methane gas absorption capacity for coal seam C of 450 SCF/ton while coal seams A, B and D of 308 SCF/ton, 336 SCF/ton and 407 SCF/ton, the fractal pore dimension value in seam coal C = 1.963 is higher than seam coal A = 1.933, B = 1.940 , and D = 1.943. The small size of the fractal pore dimension value caused by the degree of regularity of the micropore distribution in each coal seam methane differences.